THE EFFECT OF THINK PAIR SHARE TECHNIQUE ON STUDENTS’ READING COMPREHENSION: A META ANALYSIS - Deswati Maharani,; Nurpahmi, Sitti; Nur, Nur Aliyah (English Language, Linguistics, and Culture International Journal, 2023)
This research aims to analyze the effect of Think Pair Share technique on students' reading comprehension. The method used is meta analysis. Meta analysis is used to obtain the effect size value by combining several existing research results. A total of 20 published articles in the form of journals as well as theses were used as data sources, which were then analyzed. The final result of this research shows: 1) Think Pair Share technique on students' reading comprehension based on the total research findings shows a value with an average effect size of 1.747 in the very high category. 2) Think Pair Share technique on students' reading comprehension based on educational stages, both at the university, senior and junior high school stages, shows a high effect size result, but senior high school occupies the highest position in the score with an average effect size of 2.213 in the very high category. 3) Think Pair Share technique on students' reading comprehension based on regions. There are three coverage areas, namely Java, Sumatra, and Sulawesi, which occupy the highest position in the score with an average effect size of 2.172 in the very high category. It was concluded that Think Pair Share technique was effectively applied to students' reading comprehension by looking at the results of previous studies, and the findings of the effect size results in this meta analysis research were in the very high category.